Coaching livestock and fish projects on gender: Mutual learning to answer similar questions - Tyszler, Marcelo (International Livestock Research Institute, 2016)
Marcelo Tyszler is a methods and data specialist who supported some of the technical studies in this book. He saw that both the project led by Catherine Pfeifer (Putting gender on the map) and that led by Mark van Wijk (Including gender equity in a survey tool for rural households) were trying to answer similar policy questions but using different methods. The first used secondary data that were not collected with a gender focus, while the second aimed to collect gender-disaggregated primary data to answer the research question. Marcelo learned from colleagues observing new details and making sense of the complexity. Face-to-face coaching was very helpful to support the projects. Interview with Marcelo Tyszler (Royal Tropical Institute) for the book "A different kettle of fish? Gender integration in livestock and fish research": http://hdl.handle.net/10568/76684